Data Rates in EDGE Standard - Vladimir Holly; Vladimir Wieser (Advances in Electrical and Electronic Engineering, 2005)
Several modulations and coding schemes are used to reach the effective radio resources usage in EDGE networks. The review describes these methods together with base stations interference and variable quality of signal impact to data rate and used coding scheme.